POTENSI Bacillus licheniformis strain Nam 2-2 DALAM PRODUKSI BIOLISTRIK PADA VARIASI pH - Silvi Tamara Silvi; Irdawati; Linda Advinda; Elsa Yuniarti (Jurnal Biogenerasi, 2026)
The increasing global energy demand has encouraged the development of sustainable alternative energy sources such as Microbial Fuel Cells (MFCs). This study aimed to determine the optimum pH for bioelectricity production using Bacillus licheniformis strain Nam 2-2 in a dual-chamber MFC system. The experiment employed a completely randomized design with pH variations of 7, 7.5, and 8. Voltage output was measured every 2 hours over a 24-hour incubation period. The results showed that bioelectricity production increased over time, reached a peak at 16–20 hours, and then declined. The highest voltage was observed at pH 7.5, reaching 0.782 mV, followed by pH 8 (0.758 mV) and pH 7 (0.748 mV). These findings indicate that slightly alkaline conditions are more favorable for microbial activity and electron transfer efficiency. Therefore, pH optimization is essential to improve MFC performance and supports its potential as a renewable energy source.